Intraosseous primary malignant peripheral nerve sheath tumor of the calcaneus: An unusual case and review of literature - Gaurav Pratap Singh Gahlot; Asit Ranjan Mridha; Devajit Nath; Shah Alam Khan; Shivanand Gamanagatti (Wolters Kluwer Medknow Publications, 2015)
Malignant peripheral nerve sheath tumors (MPNSTs) are uncommon sarcomas that originate from a peripheral nerve or neurofibroma either spontaneously or in association with neurofibromatosis type 1. MPNSTs account for approximately 5% of all soft tissue malignancies. The tumor is commonly seen in the extremities and trunk. Most of these tumors are high-grade with the potential to recur and metastasize. Common metastatic sites include the lungs, bone, and pleura. Primary intraosseous MPNST is rare, and the diagnosis of intraosseous MPNST, especially in an unusual location is difficult because of its cellular origin, histomorphological similarities with other sarcomas, and bone is the most common site for metastasis. We report an unusual case of MPNST of the calcaneus in a young male.